2022
DOI: 10.1111/joac.12499
|View full text |Cite
|
Sign up to set email alerts
|

Labour control regimes in the rural and urban workplaces of global production networks: The coffee case of Colombia

Abstract: This study analyses the local labour control regimes (LCRs) in the workplaces of global production networks. Using the ethnographic approach, it examines the control strategies utilized by several stakeholders in coffee production and consumption sites in Colombia. The results demonstrate that transformations in the value chains have changed LCRs due to neoliberal openness and new consumption trends, which led to the creation of exploitation, discipline, and mobilization of labour practices. Rural production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This argument does not dismiss previous findings in relation to the mechanisms shaping transformations in palm oil value chain governance. States, producer organizations, local inequalities, and unions have played a crucial role composing the structure of the palm oil value chain, as previous research has identified for other industries (Baquero‐Melo, 2022; Collins, 2003; Hough, 2011; Selwyn, 2010; Talbot, 2004). However, these mechanisms by themselves cannot explain the whole range of transformations that have taken place in the palm oil value chain in Magdalena Medio over the past 60 years.…”
Section: Coercive and Indirect Labour Control Structuring Global Econ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This argument does not dismiss previous findings in relation to the mechanisms shaping transformations in palm oil value chain governance. States, producer organizations, local inequalities, and unions have played a crucial role composing the structure of the palm oil value chain, as previous research has identified for other industries (Baquero‐Melo, 2022; Collins, 2003; Hough, 2011; Selwyn, 2010; Talbot, 2004). However, these mechanisms by themselves cannot explain the whole range of transformations that have taken place in the palm oil value chain in Magdalena Medio over the past 60 years.…”
Section: Coercive and Indirect Labour Control Structuring Global Econ...mentioning
confidence: 99%
“…The conditions of local labour control regimes, on their part, are partially shaped by local inequalities in each place of production, in terms of gender, race, income, ecological conditions, and forms of State presence. Building on these inequalities, firms tend to pay less or impose more strict working conditions on marginalized groups who have few alternatives to make a living outside those industries (Baquero‐Melo, 2022; Collins, 2003; Freidberg, 2004; Pattenden, 2016; Selwyn, 2019). Moreover, labour exploitation and domination by firms produces additional fragmentation, dividing labour into formal and informal wage work, self‐employment, forced labour, family labour, and petty commodity production, with individuals and communities often fluctuating between two or more of these categories (Bernstein, 2010; Lerche, 2010; Ojeda, 2021).…”
Section: The Structure Of Value Chains and Labour Regimes In Agriculturementioning
confidence: 99%
“…Many studies of our selection are focused on establishing the effectiveness of these tools in ensuring sustainability from an ecological, social, and economic point of view [4,[8][9][10][11][12][13][14][15][16][17][18][19]. The results are contradictory.…”
Section: Certifications Geographical Indications and Origin Labelsmentioning
confidence: 99%
“…Baquero-Melo [19] analyzes the strategies utilized by several stakeholders in Colombia, highlighting that multinational roasting companies and retailers capture much of the value along the supply chain. Big corporations monopolize the supply of specialty coffee, while products with fair trade and organic certification benefit a small percentage of farmers able to take advantage of niche markets without changing the global trade distribution.…”
Section: Voluntary Sustainability Standards and Specialty Coffeementioning
confidence: 99%
See 1 more Smart Citation